Human Mesenchymal Stem Cell Sheets Improve Uterine Incision Repair in a Rodent Hysterotomy Model - Kuramoto, Goro; Hammad, Ibrahim A.; Einerson, Brett D.; Allshouse, Amanda A.; Debbink, Michelle; Grainger, David W.; Silver, Robert M.; Okano, Teruo (American Journal of Perinatology, 2020)
Objective The study aimed to assess the feasibility of creating and transplanting human umbilical cord mesenchymal stem cell sheets applied to a rat model of hysterotomy, and additionally to determine benefits of human umbilical cord mesenchymal stem cell sheet transplantation in reducing uterine fibrosis and scarring.Study Design Human umbilical cord mesenchymal stem cell sheets are generated by culturing human umbilical cord mesenchymal stem cells on thermo-responsive cell culture plates. The temperature-sensitive property of these culture dishes facilitates normal cell culture in a thin contiguous layer and allows for reliable recovery of intact stem cell sheets without use of destructive proteolytic enzymes.We developed a rat hysterotomy model using nude rats. The rat uterus has two distinct horns: one horn provided a control/untreated scarring site, while the second horn was the cell sheet transplantation site.On day 14 following surgery, complete uteri were harvested and subjected to histologic evaluations of all hysterotomy sites.Results The stem cell sheet culture process yielded human umbilical cord mesenchymal stem cell sheets with surface area of approximately 1 cm2.Mean myometrial thickness in the cell sheet-transplanted group was 274 μm compared with 191 μm in the control group (p = 0.02). Mean fibrotic surface area in the human umbilical cord mesenchymal stem cell sheet-transplanted group was 95,861 μm2 compared with 129,185 μm2 in the control group. Compared with control horn sites, cell sheet-transplanted horns exhibited significantly smaller fibrotic-to-normal myometrium ratios (0.18 vs. 0.27, respectively, p = 0.029). Mean number of fibroblasts in cell sheet-transplanted horns was significantly smaller than the control horns (483 vs. 716/mm2, respectively, p = 0.001).Conclusion Human umbilical cord mesenchymal stem cell sheet transplantation is feasible in a rat model of hysterotomy. Furthermore, use of stem cell sheets reduces fibroblast infiltration and uterine scar fibrotic tissue formation during hysterotomy healing, potentially mitigating risks of uterine scar formation.Key Points
Keywords: cell therapy; cell sheet therapy; scar repair; cesarean section; placenta accrete; uterine rupture; fibrosis; regenerative medicine